2020
DOI: 10.1155/2020/6380281
|View full text |Cite
|
Sign up to set email alerts
|

Violence against Health-Care Workers in Governmental Health Facilities in Arar City, Saudi Arabia

Abstract: Background. Violence against health-care workers (HCWs) showed increasing worldwide concern. No previous studies addressed violence against HCWs in the Northern region, Saudi Arabia. Objectives. To determine the prevalence of violence against HCWs in public hospitals and primary health-care centers in Arar city, KSA, and to identify its associated factors. Methods. A cross-sectional study was conducted on 352 HCWs in the Ministry of Health (MOH) facilities in Arar city from 1st October to 31st December 2018. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 21 publications
2
20
1
Order By: Relevance
“…This prevalence is higher than that found in previous similar studies conducted in Arar City and Abha City. In those studies, the prevalence of workplace violence among healthcare workers was 57.5% and 48.5% in Abha City [15] and Arar City [16], respectively. In other local studies that focused on a particular setting or occupation, the prevalence of workplace violence ranged between 90.7% in emergency departments in Tabuk [12] to 27.7% in primary care centers in Al-Hassa [14].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This prevalence is higher than that found in previous similar studies conducted in Arar City and Abha City. In those studies, the prevalence of workplace violence among healthcare workers was 57.5% and 48.5% in Abha City [15] and Arar City [16], respectively. In other local studies that focused on a particular setting or occupation, the prevalence of workplace violence ranged between 90.7% in emergency departments in Tabuk [12] to 27.7% in primary care centers in Al-Hassa [14].…”
Section: Discussionmentioning
confidence: 99%
“…There are a number of studies that examined workplace violence among healthcare workers in Saudi Arabia [9][10][11][12][13][14][15][16]. However, most of these studies were limited to a specific occupation like nursing [9,10], or a specific healthcare setting like emergency departments [11,12] or primary care centers [13,14].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a study conducted among 738 healthcare workers in 2 government health facility in Abha City, Saudi Arabia, 57.5% of the respondents were victims. Verbal assaults and slaps were the most common forms of violence (Al Anazi et al., 2020; Alsaleem et al., 2018). Another study conducted in a Saudi university hospital found out that almost half of the total sample quota of 360 nursing personnel had experienced violence during the 12‐month period before the study was formally conducted using the Massachusetts Survey on Workplace Violence/Abuse (Alkorashy & AL Moalad, 2016).…”
Section: Introductionmentioning
confidence: 99%